WordPress as a framework for automated data capture, filtering and structuring processes - Rodríguez-Ortega, Nuria; Cruces-Rodríguez, Antonio; Tenor-Polo, Carmen (My University, 2016)
The Exhibitium Project , awarded by the BBVA Foundation, is a data-driven project developed by an international consortium of research groups . One of its main objectives is to build a prototype that will serve as a base to produce a platform for the recording and exploitation of data about art-exhibitions available on the Internet . Therefore, our proposal aims to expose the methods, procedures and decision-making processes that have governed the technological implementation of this prototype, especially with regard to the reuse of WordPress (WP) as development framework.
WordPress como framework para la captura, filtro y estructuración de datos
Keywords: Minería de datos; Digital Art History; Digital Humanities; Technological Infrastructures; Web mining